Design of Safety Worker Helmets Based on the Internet of Things - Urmila, Tasya; Candra, Rudi Arif; Ilham, Dirja Nur; Harmayani, Harmayani; Harahap, Muhammad Khoiruddin (PERFECT: Journal of Smart Algorithms, 2024)
Safety helmets are used to protect the head from impacts, blows, or falls of sharp and heavy objects that float or slide in the air. This helmet can also protect the head from heat radiation, fire, chemical splashes, or extreme temperatures. The main benefits and uses of a safety helmet itself are to protect the worker's head, so that it can be protected from falling objects and others, and to minimize injuries that will befall the worker himself. The use of safety helmets is very much needed by workers who work in work areas such as oil mines, factories, building construction projects, and various other things. In this study, a helmet will be designed that can be used to detect the presence of its wearer with the case title Design of Safety Worker Helmets Based on the Internet Of Things, the working system of this tool is the entire series of tools from the smart helmet system to detect the location of work accidents installed on a helmet, precisely on the inside of the helmet with the position of Arduino UNO, shock sensor, GPS module, and battery in the rear position of the helmet. For the GSM module, limit switch, and tilt sensor at the top of the helmet. The voltage source from the tool is taken directly from the battery with a voltage of 12 volts.